2022
DOI: 10.1371/journal.pone.0274923
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the KC life 360 intervention: Improving employment and housing for persons living with HIV

Abstract: Housing and employment are key factors in the health and wellbeing of persons living with HIV (PLWH) in the United States. Approximately 14% of low-income PLWH report housing instability or temporary housing, and up to 70% report being unemployed. The purpose of this study was to examine the outcomes of an intervention to improve housing and employment for PLWH in the Midwest. Participants (N = 87) were recruited from the Kansas City metropolitan area to participate in a one-year intervention to improve housin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…One evaluation study of a housing and employment navigator model for families experiencing homelessness in three regions in Washington found a 7% higher rate of employment among participants who worked with a navigator specifically trained to support employment readiness, job skills and career resources [ 8 ]. Among people living with HIV, similar studies in Kansas City and New York found significant improvements in securing fulltime employment over time [ 9 , 10 ]. In these studies, a dedicated navigator/service coordinator proved effective in assessing employment skills, developing an individual employment plan with targeted goals, supporting employment readiness connection to job resources and educational training for clients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One evaluation study of a housing and employment navigator model for families experiencing homelessness in three regions in Washington found a 7% higher rate of employment among participants who worked with a navigator specifically trained to support employment readiness, job skills and career resources [ 8 ]. Among people living with HIV, similar studies in Kansas City and New York found significant improvements in securing fulltime employment over time [ 9 , 10 ]. In these studies, a dedicated navigator/service coordinator proved effective in assessing employment skills, developing an individual employment plan with targeted goals, supporting employment readiness connection to job resources and educational training for clients.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, a dedicated navigator/service coordinator proved effective in assessing employment skills, developing an individual employment plan with targeted goals, supporting employment readiness connection to job resources and educational training for clients. Navigators/coordinators also played important roles in communicating across various agencies to support a person experiencing unstable housing such as obtaining IDs, social security cards, and access to transportation [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%